Recent Advances Towards Treatment of HIV: Synthesis and SAR Studies - Shrivastava, Neelima; Husain, Asif; Rashid, Mohammad; Alsabeelah, Nimer F.; Karim, Shahid; Siddiqui, Nasir Ali (Mini Reviews in Medicinal Chemistry, 2021)
In the present study, authors want to encourage the research exertions through structureactivity relationship for the identification of effective molecules for the treatment of Human immunodeficiency virus because nowadays AIDS is considered as one of the main causes of death in human beings. A diversity of biological resources has been searched and developed for the treatment of HIV but unfortunately, until now, no medicine is found to be fully effective and safe for the cure of patients. Human immunodeficiency virus is a type of lentivirus which causes the infection of HIV and once it enters the human body, it stays for a longer period of time triggering immunodeficiency syndrome. For searching and developing new potent and effective anti-HIV molecules, medicinal chemists have engaged in countless targets with the structure-activity relationship (SAR) of molecules and on this basis, many antiretroviral therapies have been developed to cure HIV infection. Most of these new searched molecules have been found to be clinically active against various types of AIDS patient and auxiliary research in this area may lead to better treatment in the near future. This article encompasses and highlights the recent advancement of innumerable inhibitors laterally through synthetic, semi-synthetic and structure-activity relationship approaches.
Keywords: fusion inhibitors